Thrombosis and Inflammation—A Dynamic Interplay and the Role of Glycosaminoglycans and Activated Protein C - Kohli, Shrey; Shahzad, Khurrum; Jouppila, Annukka; Holthöfer, Harry; Isermann, Berend; Lassila, Riitta (Frontiers in Cardiovascular Medicine, 2022)
Hemostasis, thrombosis, and inflammation are tightly interconnected processes which may give rise to thrombo-inflammation, which is involved in infectious and non-infectious acute and chronic diseases, including cardiovascular diseases (CVD). Traditionally, due to its hemostatic role, blood coagulation is isolated from the inflammation, and its critical contribution in the progressing CVD is underrated, until the full occlusion of a critical vessel occurs. Underlying vascular injury exposes extracellular matrix to deposit platelets and inflammatory cells. Platelets being key effector cells, bridge all the three key processes (hemostasis, thrombosis, and inflammation) associated with thrombo-inflammation. Under physiological conditions, platelets remain in an inert state despite the proximity to the endothelium and other cells which are decorated with glycosaminoglycan (GAG)-rich glycocalyx (GAGs). A pathological insult to the endothelium results in an imbalanced blood coagulation system hallmarked by increased thrombin generation due to losses of anticoagulant and cytoprotective mechanisms, i.e., the endothelial GAGs enhancing anti-thrombin, tissue factor pathway-inhibitor (TFPI) and thrombomodulin-protein C system. Moreover, the loss of GAGs promotes the release of mediators, such as von Willebrand factor (VWF), platelet factor 4 (PF4), and P-selectin, both locally on vascular surfaces and to circulation, further enhancing the adhesion of platelets to the affected sites. Platelet-neutrophil interaction and formation of neutrophil extracellular traps promotes thrombo-inflammatory mechanisms exacerbating the cardiovascular disease course. Therefore, therapies which not only target the clotting mechanisms but simultaneously or independently convey potent cytoprotective effects hemming the inflammatory mechanisms are expected to provide clinical benefits. In this regard, we review the cytoprotective protease activated protein C (aPC) and its strong anti-inflammatory effects thereby preventing the ensuing thrombotic complications in CVD. Furthermore, restoring GAG-like vasculo-protection, such as providing heparin-proteoglycan mimetics to improve regulation of platelet and coagulation activity and to suppress of endothelial perturbance and leukocyte-derived pro-inflammatory cytokines, may provide a path to alleviate thrombo-inflammatory disorders in the future. The vascular tissue-modelled heparin proteoglycan mimic, APAC, dual antiplatelet and anticoagulant, is an injury-targeting and locally acting arterial antithrombotic which downplays collagen- and thrombin-induced and complement-induced activation and protects from organ injury.